A guide to conducting online research - Gaiser, Ted J.; Schreiner, Anthony E. (Los Angeles : SAGE, 2009)
This guide is designed to support students, academics and practitioner researchers in using technology as part of their research.
Introduction -- Designing an online study -- Research standards and ethical considerations -- Using email for data collection -- Researching using instant messaging and chat -- Survey research on the Internet -- The world of Web 2.0: blogs, wikis and websites -- Accessing and using Web-based data -- Analyzing the data -- Emerging research opportunities -- Presenting your results -- Some additional challenges for online researchers -- Appendix 1 : Acronyms and jargon terms -- Appendix 2 : Web links.
Includes bibliographical references (pages [168]-172) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Internet research; Internet searching; Research -- Methodology; Electronic books